Comprehensive analysis of transcriptome response to salinity stress in the halophytic turf grass Sporobolus virginicus - Yamamoto, Naoki; Takano, Tomoyuki; Tanaka, Keisuke; Ishige, Taichiro; Terashima, Shin; Endo, Chisato; Kurusu, Takamitsu; Yajima, Shunsuke; Yano, Kentaro; Tada, Yuichi (Frontiers in Plant Science, 2015)
The turf grass Sporobolus virginicus is halophyte and has high salinity tolerance. To investigate the molecular basis of its remarkable tolerance, we performed Illumina high-throughput RNA sequencing on roots and shoots of a S. virginicus genotype under normal and saline conditions. The 130 million short reads were assembled into 444,242 unigenes. A comparative analysis of the transcriptome with rice and Arabidopsis transcriptome revealed six turf grass-specific unigenes encoding transcription factors. Interestingly, all of them showed root specific expression and five of them encode bZIP type transcription factors. Another remarkable transcriptional feature of S. virginicus was activation of specific pathways under salinity stress. Pathway enrichment analysis suggested transcriptional activation of amino acid, pyruvate, and phospholipid metabolism. Up-regulation of several unigenes, previously shown to respond to salt stress in other halophytes was also observed. Gene Ontology enrichment analysis revealed that unigenes assigned as proteins in response to water stress, such as dehydrin and aquaporin, and transporters such as cation, amino acid, and citrate transporters, and H+-ATPase, were up-regulated in both shoots and roots under salinity. A correspondence analysis of the enriched pathways in turf grass cells, but not in rice cells, revealed two groups of unigenes similarly up-regulated in the turf grass in response to salt stress; one of the groups, showing excessive up-regulation under salinity, included unigenes homologous to salinity responsive genes in other halophytes. Thus, the present study identified candidate genes involved in salt tolerance of S. virginicus. This genetic resource should be valuable for understanding the mechanisms underlying high salt tolerance in S. virginicus. This information can also provide insight into salt tolerance in other halophytes.